Faktor Internal (Heriditas Dan Gizi) Mempengaruhi Perkembangan Manusia - Sahbana, M. Dwi Rahman (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2024)
The purpose of this research is to analyze the factors that influence human development. The author conducts research using literature study whose subject is literary literature. The results of the research conducted by the author, namely, internal factors play an important role and certainly influence human development. In this study, there are two components of factors that influence this development, namely heredity and nutrition. With these two components, the author analyzes the internal factors that influence human development. The first results of this research are that heridity can simply be said to be genetic inheritance, both physically and in terms of its characteristics, therefore heredity cannot be denied as a determinant in the formation of human personality and human development. Children are born with certain talents, these talents can be likened to seeds of ability or seeds of possibility contained in the child which are inborn. And if given education or support for these talents, it will affect the development of each individual. Second, the assessment of the nutritional status of toddlers can be measured based on anthropometric measurements consisting of the variables age, weight (BB) and height (TB). According to UNICEF, there are three causes of malnutrition in children, namely direct causes, indirect causes and underlying causes. Inadequate nutrition also has an impact on brain development and intellectual capacity during a critical period of growth which causes a decrease in intelligence. If inadequate intake of nutrients continues and gets worse, it can cause death in children.